Challenges in Translating Chinese Classics into English: Example of Biography of Huan Tan and Feng Yan from Book of the Later Han (Sinología hispánica. China Studies Review, 2019)
As one of the Early Four Historiographies, Fan Ye’s Book of the Later Han preserves significant works of both historical and literary value. This is something increasingly significant in response to the dynamic growth in popularity of classical Chinese texts among Western sinologists. Through reading the English translation of the “Biography of Huan Tan and Feng Yan” from the Book of the Later Han, the followingthree issues are arguably noteworthy for the translator’s consideration. Firstly, the English translation may involve aninterim step of intralingual translation from classical Chinese to modern Chinese, before a subsequent interlingual translation from modern Chinese to English. While this facilitates the process of translation,the vernacular translation also involves further risks in misinterpretation. Secondly, translation of such historiographical work which consists of literary works by various writers with numerous historical references,not only requires the translator to conduct additional analysis and write explanatory notes, it also makes the English output inaccessible to most readers. Thirdly,the highly interdisciplinary knowledge in relevant historiography not only demands a high quality of competency in translators, but also arguably acts as a catalyst for further academic research in the process of close reading and research. This paper intends to analyse the above three issues through a case study on the “Biography of Huan Tan and Feng Yan”, thereby demonstrating how the translation of Chinese classics is anarduous yet meaningful challenge.